PELAYANAN PASTORAL YANG MELIBATKAN TUBUH: INTEGRASI ANTARA KATA DAN TUBUH - Pauline Patricia (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2019)
This paper proposes an integrated pastoral service model. I begin with a fundamental question, what kind of pastoral care is right for people who are traumatized? Pastoral care with the dimension of voice and words will certainly be very difficult for those who are unable to speak their wound experience. Because, trauma causes someone's memory and life to be fragmented, making it difficult for them to be open and tell stories. Therefore, integrated pastoral care between verbatim and psycho-physiotherapy can be an alternative for counselors dealing with those who have experienced trauma. This paper will begin with the reality of the wound that does not always allow anyone to speak verbally. Next, I will frame pastoral care which involves anesthetic-therapeutic dimension as an alternative. Finally, this paper will conclude with conclusions and reflections.